2017
DOI: 10.1002/path.4867
|View full text |Cite
|
Sign up to set email alerts
|

PAX3–FOXO1 is essential for tumour initiation and maintenance but not recurrence in a human myoblast model of rhabdomyosarcoma

Abstract: The PAX3-FOXO1 fusion gene is generated by a 2;13 chromosomal translocation and is a characteristic feature of an aggressive subset of rhabdomyosarcoma (RMS). To dissect the mechanism of oncogene action during RMS tumourigenesis and progression, doxycycline-inducible PAX3-FOXO1 and constitutive MYCN expression constructs were introduced into immortalised human myoblasts. Though myoblasts expressing PAX3-FOXO1 or MYCN alone were not transformed in focus formation assays, combined PAX3-FOXO1 and MYCN expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 33 publications
2
75
0
Order By: Relevance
“…They discovered that FILNC1 represses c‐Myc‐mediated energy metabolism and inhibits renal tumor development . Additionally, studies have also demonstrated that FOXO1 has antitumor actions in spindle cell lipoma, rhabdomyosarcomas and Kaposi's sarcoma (Table ).…”
Section: Roles Of Foxo1 In Diverse Human Neoplasmsmentioning
confidence: 99%
“…They discovered that FILNC1 represses c‐Myc‐mediated energy metabolism and inhibits renal tumor development . Additionally, studies have also demonstrated that FOXO1 has antitumor actions in spindle cell lipoma, rhabdomyosarcomas and Kaposi's sarcoma (Table ).…”
Section: Roles Of Foxo1 In Diverse Human Neoplasmsmentioning
confidence: 99%
“…One important pitfall of using the tumor‐specific fusion gene as a biomarker is the possibility of the tumor progressing to a fusion‐independent state due to the acquisition of other genetic abnormalities after therapeutic interventions are performed for the primary tumor. The actual progression to a PAX3‐FOXO1 ‐independent state during the recurrence of the tumor has been reported recently in a mouse model . Therefore, fusion‐specific assays may become problematic in the later stages of tumor progression in some cases, particularly in settings involving treatment with targeted agents that may enhance clonal selection inside the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 (exon 2) 0 6 3 0 5 3 0 4 3 0 3 3 0 2 3 0 1 3 0 0 3 0 9 2 0 8 2 0 7 2 0 6 2 0 5 2 during the recurrence of the tumor has been reported recently in a mouse model. 22 Therefore, fusion-specific assays may become problematic in the later stages of tumor progression in some cases, particularly in settings involving treatment with targeted agents that may enhance clonal selection inside the tumors.…”
Section: Quantification Of the Pax3-foxo1 Fusion Gene In Blood Plasmentioning
confidence: 99%
“…This and previous functional work show cell death and differentiation results from ablation of the fusion protein in tumour‐derived cells and have led to the view that the fusion protein is an Achilles heel of ARMS. The work carried out by Pandey et al is the first to test the reliance of these tumours on the fusion gene in vivo beyond the stage of tumour initiation. They mimicked a targeting strategy by reducing levels of the fusion protein in an established tumour model and discovered that despite a dramatic initial response, tumours recurred that in some cases lacked PAX3–FOXO1 expression.…”
mentioning
confidence: 99%
“…Model of alveolar rhabdomyosarcoma demonstrating that PAX3–FOXO1‐independent recurrences can arise from PAX3–FOXO1‐expressing primary tumours. Pandey et al have shown that tumours and in vitro transformed clones arise when MYCN is constitutively expressed and PAX3–FOXO1 is induced in immortalized human myoblasts in an orthotopic xenograft model ( in vivo ). These regress when PAX3–FOXO1 expression is switched off; however, they recur in two ways: firstly, when cells re‐express the fusion gene (PAX3–FOXO1‐dependent); and, secondly, via a PAX3–FOXO1‐independent mechanism.…”
mentioning
confidence: 99%